Rotas alteradas: trajetórias e significados da esterilização para mulheres atendidas no Serviço de Planejamento Familiar-SPF do SUS municipal de Cuiabá-MT - Macaúbas, Ademar Sales (2011)
The objective of this work is to identify and analyze the repercussions and meanings of the female sterilization in the life trajectory of the women and their husbands/partners attended by the Family Planning Service-SPF of the Policlínica Dr. Henrique de Aquino CPA I, in Cuiabá (MT). The main strategy of the investigation was the analysis centered in the decision process for the surgery of tubal ligature, among the set of contraceptives currently made available for men and women. With the execution of a exploratory examination, of quali-quantitative nature, on the social conditions and the motivation for seeking the SPF, of a group of 130 women, between the years 2006 and 2008, we started from the basic point that it is the woman who takes the initiative of seeking the intervention and, for the most part, assumes the burden of the decision, besides the risk of the surgical process in her own body. The listening to these women was privileged among the set of procedures of data collecting, through the use of qualitative techniques, specially the oral history resources. Focusing the interview on the moment of decision, significant and correlated situations were approached: infancy, teenage; work and income; maternity; sexuality and conjugality; knowledge, attributed meanings and use of contraceptives methods; main changes perceived after the surgical procedure; besides, specially, of the description and meaning attributed to what determined it, impacts and consequences of the sterilization. Men were also heard, as co actors in the reproductive process, standing out the importance of their comprehension of the option for the vasectomy as a method. As for the results, are outstanding: the diversified consequences on the sexual activity and self image of their performance, from living with more liberty and better enjoyment of the pleasure to the decrease and disappearance of the sexual desire; clear misinformation about the STDs/Aids and the need and possibility of safe sex; the strong desire to be a mother, of personal and cultural basis, also among the efficient factors of taming of the bodies, delaying sterilization, even in limit situations of risks; the recognized importance of the SPF, with a negative evaluation of the attendance, in terms of confidence and tranquility in the processing of the demands and the carrying out of the surgical intervention; difficulties pointed out between the comprehension of the legislation and the singular demands. Thus, the conclusions are towards that, even if the knowledge, by the studied population, can be characterized as of low control and mistakes of interpretation, the decision to make the ligature is, for the most part, connected to a conscious and coherent life project with the exit from the minimum level of survival and of the accomplishing of impossible aspirations, at least in the short term horizon of work pay and of the structures of social protection. Therefore, the objective is to significantly change the trajectories of the women, children and husbands/partners lives, with the overcoming of many obstacles